Comparative analysis of different methods for protein quantification in donated human milk - Navarro-Tapia, Elisabet; Herranz Barbero, Ana; Marquina, Maribel; Borràs-Novell, Cristina; Pleguezuelos, Vanessa; Vila-Candel, Rafael; García-Algar, Óscar; Andreu-Fernández, Vicente (Frontiers in Pediatrics, 2024)
Background: Human milk is the best option for the feeding of all newborns, especially in premature infants. In the absence breast milk, milk from a human milk bank (HMB) can be a suitable alternative. However, the nutritional content of human milk may be insufficient to meet these high requirements and milk fortification is needed. To facilitate the implementation of simpler and faster analysers in neonatal healthcare facilities, this study focuses on the concordance analysis of two different analysers based on mid-infrared (MIR) and ultrasound in comparison to the Bradford method for the determination of protein concentration in human milk. Methods: Mature milk samples from donor mothers were collected and pasteurised at the Human Milk Bank of Barcelona and protein quantification was performed using mid-infrared (MIRIS-HMA), ultrasound (MilkoScope Julie27) and the classical Bradford reference method. The intraclass correlation coefficient (ICC) with 95% confidence interval and Bland-Altman plots were used to assess the agreement between methods. Results: The mean protein concentration of 142 milk samples by MIRIS-HMA, MilkoScope and Bradford assay were 1.38, 1.15, and 1.19 g/100mL, respectively. The ICC was 0.70 for MIRIS-HMA vs. Bradford and 0.37 for MilkoScope vs. Bradford. Conclusions: MIRIS-HMA obtained a better agreement with the Bradford technique and is a promising technique for the development of new devices based on mid-infrared transmission spectroscopy principles. This study confirms how MIRIS-HMA can be used to accurately calculate the protein concentration of human milk.